The works of Ha-Joon Chang - Jahangir, Junaid (My University, 2024)
Over the last 20 years, Ha-Joon Chang has weaved a consistent narrative in popular books from Kicking Away the Ladder in 2002 to Edible Economics in 2022. His body of work challenges the narrative in mainstream textbook economics. While his focus is on free trade, foreign direct investment, and neoliberalism, he offers interesting insight on the role of culture in economic development and why poor people in poor countries are poor. His narrative is very much welcome in a time with calls for economic pluralism in the pedagogy of economics.
Keywords: economics; neoclassical economics; economic development; free trade; neoliberalism; economic inequality